In vivo Evidence for Partial Activation of Eosinophils via the Histamine H4-Receptor: Adoptive Transfer Experiments Using Eosinophils From H4R−/− and H4R+/+ Mice - Schirmer, Bastian; Bringmann, Luisa; Seifert, Roland; Neumann, Detlef (Frontiers in Immunology, 2018)
Our previous in vitro studies revealed that histamine via histamine H4-receptors (H4R), as compared to other stimuli such as eotaxin or formylpeptides, rather incompletely activates eosinophilic granulocytes (eosinophils). In order to evaluate the H4R-mediated activation of eosinophils in vivo, we employed dextran sodium sulfate (DSS)-induced colitis in mice, closely resembling human ulcerative colitis (UC), which is largely characterized by a local eosinophilic infiltration of the colon. IL-5-deficient BALB/c mice served as a model with reduced endogenous numbers of eosinophils, in which wild-type (H4R+/+) or H4R-deficient (H4R-/-) eosinophils were adoptively transferred during the course of DSS-induced colitis. Analyzing clinical and pathological parameters representative of colitis, we demonstrate that also in vivo histamine via the H4R only incompletely activates eosinophils.